Stimulation of Small and Medium-Sized Enterprises - Aliyeva Aygun Akbar, (Technium Social Sciences Journal, 2020)
The paper deals with the issues of stimulating small and medium-sized enterprises in Azerbaijan. The conducted analysis shows that sustainable reforms carried out in the country on the basis of international business experience are considered very effective. The existing problems in this area have also been analyzed, and the directions for their elimination have been indicated.